Performance Index of Natural Stones-GFRP Hybrid Structures (Fracture and Structural Integrity, 2018)
Natural stone is a material that presents durableness over time and high aesthetic characteristic, but it is brittle and its tensile strength is significantly lower than compressive one: these peculiarities must be taken into account for material usage; in fact, for applications requiring high flexural and tensile strength, as thin sections or long spans, the particular mechanical behavior of the natural stone constitutes an issue to be overcome.A solution to the above mentioned problem is presented in the present paper: a natural stone tile is reinforced by bonding a sandwich structural laminate made of composite materials. In such manner, a double result is obtained: the mechanical strength increment and the and the tile specific weight decrement. In particular, two different types of sandwich structures, made of glass/epoxy laminates and honeycomb or foam core, were bonded to the lower surfaces of marble and granite tiles; then, 3-point bending tests were carried out on specimens extracted from the produced hybrid tiles. A performance index, considering both strength and weight of tiles, was introduced and the comparison with specimens extracted from traditional unreinforced tiles demonstrated that the considered reinforcement increases the structural characteristics of stone tiles up to an order of magnitude.
Keywords: Natural stones; Glass/epoxy sandwich laminate; 3-point bending test; Structural behavior improvement